FRI0129 Pro-atherogenic chemokines and TNF-alpha family cytokines in rheumatoid arthritis patients treated with atorvastatin. (23rd January 2014) - Rupinski, R.; Lewandowski, Z.; Walewska, E.; Filipowicz-Sosnowska, A.; Gluszko, P.
Abstract : Background: Certain chemokines and TNF-α family cytokines participate in the development of atherosclerosis and in the pathogenesis of rheumatoid arthritis (RA). Early-onset and severe atherosclerosis is responsible for high incidence of cardiovascular diseases in RA patients. Objectives: To investigate the impact of low-cholesterol diet and statin treatment on serum concentration of selected chemokines: CX3 CL1 (Fraktalkine), CCL2 (MCP-1), CCL5 (RANTES) and TNF-α family cytokines: TNF-α, CD40-ligand, FAS-ligand, in patients with RA and hypercholesterolaemia. Methods: 74 mostly female (93.2%) RA patients, age 59.4±7.3 years, disease duration 8.9±8.4 years, anti-CCP positive 69.8%, disease activity score (DAS28) 3.63±1.15, with serum total cholesterol (TCh) above 200 mg/dl (mean 246±33 mg/dl) were included in the study. All patients participated in a recommended low-cholesterol diet therapy and 36 patients (48.7%) received additional atorvastatin treatment (10 mg daily), according to the ATP III guidelines [1]. Atherogenicity index (AI = TCh/HDL-cholesterol) was calculated and serum concentration of CX3 CL1, CCL2, CCL5, TNF-α, CD40-ligand, and FAS-ligand was measured using ELISA (R&D Systems) before and after 4 months of treatment. Statistical analysis was performed using general linear models (SAS System v. 9.3). Results: Statistically significant AI decrease after 4 months (4.70 vs 3.63) was observed in the group treated with atorvastatin, but not in the patients with dietary treatment only (3.32 vs 3.76, p<0.001 for interaction effect). CCL5 concentration decreased similarly in both groups during the study (p<0.0001 for time effect). CD40-ligand concentration increased significantly only in the diet group, but in the atorvastatin group it remained unchanged during the trial (p<0.0001 for interaction effect). No differences were observed in the serum concentrations of CX3 CL1, CCL2, TNF-α, FAS-ligand before and after the treatment in both groups. Conclusions: Atorvastatin treatment influencing serum lipids and lowering atherogenicity index in patients with RA, simultaneously decreases serum level of pro-atherogenic chemokine CCL5 and prevents increase of CD40-ligand concentration. Diet treatment alone does not seem to influence pro-atherogenic factors in RA. References: Third Report of the National Cholesterol Education Program (NCEP) Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults (Adults Treatment Panel III). Circulation 2002; 106: 3143. Disclosure of Interest: None Declared